2016
DOI: 10.3390/su8060539
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Life Cycle Greenhouse Gas Emissions from Hydroelectricity Generation Systems

Abstract: This study evaluated the life cycle greenhouse gas (GHG) emissions from different hydroelectricity generation systems by first performing a comprehensive review of the hydroelectricity generation system life cycle assessment (LCA) studies and then subsequent computation of statistical metrics to quantify the life cycle GHG emissions (expressed in grams of carbon dioxide equivalent per kilowatt hour, gCO 2 e/kWh). A categorization index (with unique category codes, formatted as "facility type-electric power gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The Cuenca metropolitan area is the third largest city in Ecuador with a total area of 3665.32 km 2 [22] and a total population of 505,585 in 2010. However, the urban centre amidst this large cantonal area was a mere 66.71 km 2 in 2010 [20].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cuenca metropolitan area is the third largest city in Ecuador with a total area of 3665.32 km 2 [22] and a total population of 505,585 in 2010. However, the urban centre amidst this large cantonal area was a mere 66.71 km 2 in 2010 [20].…”
Section: Methodsmentioning
confidence: 99%
“…The methodological approach proposed in this paper is potentially particularly useful for local governments world-wide which face a scarcity of financial resources and technical expertise. Other studies have focused on the interrelationship between the water and energy sectors at the urban level and in particular on the technologies and interventions that have the potential to improve the sustainable management of scarce natural resources [16][17][18]22,23]. Firstly, a major gap identified in these studies is the lack of integration of the various approaches taken to study the dynamics of multiple water-energy interlinkages.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanafi and Riman assessed the life cycle of a mini hydropower plant in Simalungun, Indonesia, with results showing that both carcinogenic marine and freshwater aquatic eco-toxicity are the highest environmental effects generated from the construction of such hydropower plants [17]. Kadiyala et al evaluated the life cycle GHGs emissions from different hydroelectricity generation systems [18]. Pascale et al assessed the life cycle of a community hydropower system in rural Thailand; the results suggested that small-scale hydropower was more environmentally friendly than diesel generators and grid connection alternatives, considering mostly economic and social factors.…”
Section: Introductionmentioning
confidence: 99%
“…PHES systems typically operate with low-cost off-peak or excess electricity to pump water from a lower to an upper reservoir (either natural or artificial) in order to use the stored potential energy of the water for electricity generation upon system demand [5]. These systems are characterized by round-trip efficiency in the range of 70-80%, while figures reaching 87% are also reported in the literature [6].…”
Section: Introductionmentioning
confidence: 99%